2015
DOI: 10.3390/agronomy5030435
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Role of Fungicides and Plant Growth Regulator (Trinexapac) on Seed Yield and Oil Quality of Winter Rapeseed

Abstract: This study was designed to evaluate the role of growth regulator trinexapac and fungicides on growth, yield, and quality of winter rapeseed (Brassica napus L.). The experiment was conducted simultaneously at different locations in Germany using two cultivars of rapeseed. Five different fungicides belonging to the triazole and strobilurin groups, as well as a growth regulator trinexapac, were tested in this study. A total of seven combinations of these fungicides and growth regulator trinexapac were applied at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Fungicides are among the most important and most commonly used groups of pesticides, which are applied to protect plants against fungal diseases. They contain one or more active substances, the action of which in fungal cells includes: arrest of mitosis and cell division; inhibition of respiration, synthesis of nucleic acids, amino acids and proteins, lipids and cell membranes, as well as cell wall melanin, but also inhibition of sterol and cell wall biosynthesis, and signal transduction (Petit et al 2012 ; Ijaz et al 2015 ). Fungicides primarily allow obtaining high plant yields, but they can also exert negative effects on the environment, including the soil, by disrupting its homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Fungicides are among the most important and most commonly used groups of pesticides, which are applied to protect plants against fungal diseases. They contain one or more active substances, the action of which in fungal cells includes: arrest of mitosis and cell division; inhibition of respiration, synthesis of nucleic acids, amino acids and proteins, lipids and cell membranes, as well as cell wall melanin, but also inhibition of sterol and cell wall biosynthesis, and signal transduction (Petit et al 2012 ; Ijaz et al 2015 ). Fungicides primarily allow obtaining high plant yields, but they can also exert negative effects on the environment, including the soil, by disrupting its homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Homogenous groups denoted with letters (a-k) were calculated separately for each enzyme and for each type of biostimulating substance Te-tebuconazole; Deh-dehydrogenases; Cat-catalase; Ure-urease; Pac-acid phosphatase; Pal-alkaline phosphatase; Glu-β-glucosidase; Aryl-arylsulfatase, r-Pearson's correlation coefficient preparations. Also, Ijaz et al (2015) in their study with Torpex, Folicur, Proline, Caramba, Otrivia, and Cantus preparations confirmed the fact that when fungicides are applied following producers' recommendations, they may increase the yield of crops, including winter rapeseed investigated in their study. In our experiment, compost and bird droppings turned out to be ineffective in improving spring barley yield.…”
Section: Spring Barley Yieldmentioning
confidence: 52%
“…Inclusion of the fungicide Caramba (a.i. metconazole 8.6 %) improved the yield-associated parameters (the number of siliques and the seeds per main stem) and seed yield, and also resulted in higher oil content (Ijaz et al, 2015).…”
Section: Resultsmentioning
confidence: 99%